2013
DOI: 10.1002/cne.23217
|View full text |Cite
|
Sign up to set email alerts
|

Distinct abnormalities of the primate prefrontal cortex caused by ionizing radiation in early or midgestation

Abstract: Prenatal exposure of the brain to environmental insult causes different neurological symptoms and behavioral outcomes depending on the time of exposure. To examine the cellular bases for these differences, we exposed Rhesus macaque fetuses to x-rays during early gestation (E30–E42), i.e., before the onset of corticogenesis, or in midgestation (E70–E81) when superficial cortical layers are generated. Animals were delivered at term (~E165), and the size and cellular composition of prefrontal association cortex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 65 publications
3
32
0
2
Order By: Relevance
“…Thalamic neuron number overall and in the mediodorsal nucleus is reduced in fetally irradiated monkeys (FIMs) (Selemon et al, 2009); reduction of neuron number in the mediodorsal nucleus has also described in brains from schizophrenic subjects (Pakkenberg, 1990; Young et al, 2000; Popken et al, 2000). The dorsolateral prefrontal cortex in FIMs is characterized by diminished cortical surface area but not thickness (Selemon et al, 2013), as has been reported in schizophrenic subjects (Guttlerez-Galve et al, 2010). We have also found abnormally high cortical neuronal density in the dorsolateral prefrontal cortex of FIMs (Selemon et al, 2013), a finding analogous to that in postmortem studies of schizophrenic brains (Selemon et al, 1995; 1998; 2003).…”
mentioning
confidence: 57%
“…Thalamic neuron number overall and in the mediodorsal nucleus is reduced in fetally irradiated monkeys (FIMs) (Selemon et al, 2009); reduction of neuron number in the mediodorsal nucleus has also described in brains from schizophrenic subjects (Pakkenberg, 1990; Young et al, 2000; Popken et al, 2000). The dorsolateral prefrontal cortex in FIMs is characterized by diminished cortical surface area but not thickness (Selemon et al, 2013), as has been reported in schizophrenic subjects (Guttlerez-Galve et al, 2010). We have also found abnormally high cortical neuronal density in the dorsolateral prefrontal cortex of FIMs (Selemon et al, 2013), a finding analogous to that in postmortem studies of schizophrenic brains (Selemon et al, 1995; 1998; 2003).…”
mentioning
confidence: 57%
“…Estimates of neuronal and glial densities in different cortical regions have been obtained from several histopathological studies in humans and mammals. Altered measures have been suggested as explanations for cortical thinning observed at the macroscopic level in other neuroimaging studies (37, 38). …”
Section: Discussionmentioning
confidence: 86%
“…However, no definitive conclusion can be reached until LCDM analysis can be correlated with measures in histopathological MRI studies of SCZ [e.g., Ref. (38)].…”
Section: Discussionmentioning
confidence: 99%
“…Despite important advances in the understanding of brain and cortical development 40, 41 , our knowledge regarding the cellular, biochemical, and electrophysiological processes directing this interplay still remains fragmentary 42 . On the other hand, even minor disturbances during this susceptible and delicate process can have significant consequences 43, 44 , and there is evidence for a strict regulation and temporal limitation of structured postnatal neurogenesis 45 . This may, at least partly, account for the observation of teratomas 46 or teratocarcinomas 47 after transplantation of pluripotent stem cells into the adult mammalian brain.…”
Section: Part Ii: Recovery Without Replacement and The Prevalence Of mentioning
confidence: 99%